POS SERVICES COMBINED (POSYANDU) EFFICIENCY IN STUNTING PROTECTION IN PURWANEGARA DANGER PURWOKERTO NORTH BANYUMAS - Rifdah Luthfitah; Andri Trianfano; Johar Mamuri (DYNAMICS: Journal of Public Administration, 2023)
Stunting is a nutritional health problem that must be addressed immediately because theimpacts are not only short-term but also long-term. The long-term impact or stunting can threaten the quality of human resources in the future. One area that has a fairly high stunting rate is Purwanegara Village, Purwokerto Utara District. The steps taken by the government to deal with stunting are optimizing the role of posyandu. One of the roles that is considered to be able to help deal with stunting in Purwanegara Village is the role of posyandu in providing health counseling and counseling nutrition whose goal is to increase awareness and knowledge of mothers under five so that there is a change in behavior for the better (;).